The Reference Forward Model (RFM). (January 2017) - Dudhia, Anu
Abstract: The Reference Forward Model (RFM) is a general purpose line-by-line radiative transfer model, currently supported by the UK National Centre for Earth Observation. This paper outlines the algorithms used by the RFM, focusing on standard calculations of terrestrial atmospheric infrared spectra followed by a brief summary of some additional capabilities and extensions to microwave wavelengths and extraterrestrial atmospheres. At its most basic level — the 'line-by-line' component — it calculates molecular absorption cross-sections by applying the Voigt lineshape to all transitions up to ±25 cm −1 from line-centre. Alternatively, absorptions can be directly interpolated from various forms of tabulated data. These cross-sections are then used to construct infrared radiance or transmittance spectra for ray paths through homogeneous cells, plane-parallel or circular atmospheres. At a higher level, the RFM can apply instrumental convolutions to simulate measurements from Fourier transform spectrometers. It can also calculate Jacobian spectra and so act as a stand-alone forward model within a retrieval scheme. The RFM is designed for robustness, flexibility and ease-of-use (particularly by the non-expert), and no claims are made for superior accuracy, or indeed novelty, compared to other line-by-line codes. Its main limitations at present are a lack of scattering and simplified modelling of surface reflectance and line-mixing. Abstract : Highlights: The RFM is a general purpose line-by-line radiative transfer model. The RFM creates spectra of infrared radiance and transmittance. The paper describes the underlying algorithms used by the RFM. The RFM is designed to be robust, portable and flexible.